Confederate Monuments and Democratic Practice in the Classroom - Bohan, Chara Haeussler; Bradshaw, Lauren Yarnell; Pecore, John L (Schools (Chicago, Ill.), 2023)
In the United States of America, democratic education has evolved philosophically over 200 years from Jeffersonian ideas of educated citizenry to Deweyan principles of democracy as a "mode of associated living." In contemporary society, Dianna Hess has written about democratic education as a process of deliberative democracy. Yet the idea of democratic education remains challenging to implement in actual classrooms. In this article, we focus on one teacher's practice of introducing the topic of Confederate monuments in a Georgia history classroom. Then, we explore how philosophical theories of democratic education help teachers guide students as they encounter controversial issues. Although democracy is viewed by contemporary philosophers of education as a social construct that must be cared for primarily by educators, placing the responsibility for democracy solely on teachers through democratic classroom practices is unrealistic. However, by implementing democratic pedagogies to foster active student decision-making and deliberative skills in a respectful environment that values diversity, students and teachers can embark on a mode of associated living that values democracy. We conclude with recommendations to assist teachers who want to practice democratic education.